Relationship Between Amoxicillin Use in Pregnancy and Congenital Anomalies: A Systematic Review - Bahri, Narjes; Dashti, Sareh; Mohammadzadeh, Alireza; Sharifi, Neda; Hadizadeh-Talasaz, Fatemeh; Mardeneh, Jalal (Current Drug Research Reviews, 2023)
Objective: Amoxicillin is among the most used antibiotics in the treatment of a wide spectrum of bacterial infections. Although amoxicillin is categorized as group B in pregnancy, the findings of studies regarding its effects on the fetus are controversial. The aim of this systematic review was to review the reported effects of amoxicillin administration in pregnancy on congenital anomalies. Methods: Published articles in PubMed, Scopus, SID, and Magiran databases, as well as Google Scholar were searched till May 2021 based on a search strategy. Case-control and cohort studies in Persian or English language were included. Four studies, including two case-control and two cohort studies, with an overall sample size of 260491 pregnant mothers, were included in the review. Results: A review of case-control studies revealed an increased risk for cleft palate in one study. Cohort studies did not reveal a significant relationship between amoxicillin use and major congenital anomalies. Conclusion: The findings of this systematic review showed that although no major congenital anomaly was reported for the administration of amoxicillin consumption with or without clavulanic acid, there is a possibility that amoxicillin administration in pregnancy might be related to some anomalies, including cleft palate. Amoxicillin should be administered with caution during pregnancy till more evidence is provided regarding its safety.
Keywords: clavulanic acid